Clinical initiatives linking Japanese and Swedish healthcare resources on cancer studies utilizing Biobank Repositories. Issue 1 (22nd November 2014) - Nishimura, Toshihide; Kawamura, Takeshi; Sugihara, Yutaka; Bando, Yasuhiko; Sakamoto, Shigeru; Nomura, Masaharu; Ikeda, Norihiko; Ohira, Tatsuo; Fujimoto, Junichiro; Tojo, Hiromasa; Hamakubo, Takao; Kodama, Tatsuhiko; et al.
Abstract: The Tokyo Medical University Hospital in Japan and the Lund University hospital in Sweden have recently initiated a research program with the objective to impact on patient treatment by clinical disease stage characterization (phenotyping), utilizing proteomics sequencing platforms. By sharing clinical experiences, patient treatment principles, and biobank strategies, our respective clinical teams in Japan and Sweden will aid in the development of predictive and drug related protein biomarkers. Data from joint lung cancer studies are presented where protein expression from Neuro‐ Endocrine lung cancer (LCNEC) phenotype patients can be separated from Small cell‐ (SCLC) and Large Cell lung cancer (LCC) patients by deep sequencing and spectral counting analysis. LCNEC, a subtype of large cell carcinoma (LCC), is characterized by neuroendocrine differentiation that small cell lung carcinoma (SCLC) shares. Pre‐therapeutic histological distinction between LCNEC and SCLC has so far been problematic, leading to adverse clinical outcome. An establishment of protein targets characteristic of LCNEC is quite helpful for decision of optimal therapeutic strategy by diagnosing individual patients. Proteoform annotation and clinical biobanking is part of the HUPO initiative (http://www.hupo.org ) within chromosome 10 and chromosome 19 consortia.